Implementation Cascade of a Social Network-Based HIV Self-testing Approach for Men Who Have Sex With Men: Cross-sectional Study - Tsz Ho Kwan; Denise Pui Chung Chan; Samuel Yeung-shan Wong; Shui Shan Lee (JMIR Publications, 2023)
BackgroundHIV testing is the cornerstone of strategies for achieving the fast-track target to end the AIDS epidemic by 2030. Self-testing has been proven to be an effective health intervention for men who have sex with men (MSM). While social network-based approaches for distributing HIV self-tests are recommended by the World Health Organization, their implementation consists of multiple steps that need to be properly evaluated. ObjectiveThis study aimed to assess the implementation cascade of a social network-based HIV self-test approach for reaching MSM who had never undergone testing in Hong Kong. MethodsThis is a cross-sectional study. Seed MSM participants were recruited through different web-based channels, who in turn invited their peers to participate in this study. A web-based platform was set up to support the recruitment and referral process. Participants could request for an oral fluid or a finger-prick HIV self-test, with or without real-time support, after completing a self-administered questionnaire. Referrals could be made upon uploading the test result and passing the web-based training. Characteristics of participants completing each of these steps and their preferences for the type of HIV self-test were evaluated. ResultsA total of 463 MSM were recruited, including 150 seeds. Participants recruited by seeds were less likely to have previously been tested for HIV (odds ratio [OR] 1.80, 95% CI 1.06-3.04, P=.03) and have lower confidence in performing self-tests (OR 0.66, 95% CI 0.45-0.99, P=.045). Almost all (434/442, 98%) MSM who completed the questionnaire requested a self-test, of whom 82% (354/434) had uploaded their test results. Participants requesting support were new to self-testing (OR 3.65, 95% CI 2.10-6.35, P<.001) and less confident in carrying out the self-test correctly (OR 0.35, 95% CI 0.22-0.56, P<.001). More than half (216/354, 61%) of the eligible participants initiated the referral process by attempting the web-based training with a passing rate of 93% (200/216). They were more likely to have sought sex partners (OR 2.20, 95% CI 1.14-4.25, P=.02), especially through location-based networking apps (OR 2.13, 95% CI 1.31-3.49, P=.002). They also gave higher usability scores along the implementation cascade (median 81 vs 75, P=.003). ConclusionsThe social network approach was effective in diffusing HIV self-tests in the MSM community and reaching nontesters. Support and option to choose a preferable type of self-test are essential to address users' individual needs when delivering HIV self-tests. A positive user experience throughout the processes along the implementation cascade is vital to transform a tester into a promoter. Trial RegistrationClinicalTrials.gov NCT04379206; https://clinicaltrials.gov/ct2/show/NCT04379206